Ecologo-Geochemical Conditions of the Water Bodies Within the Damodar River Basin (India) During a Low-Water Period; Geography and Natural Resources; Vol. 41, iss. 3 - Savichev O. G. Oleg Gennadievich; Soldatova E. A. Evgeniya Aleksandrovna; Chaudhuri H. Hirok; Ivanova I. S. Irina; Ulaeva S. S. Svetlana Sergeevna (2020, 2020)
Title screen